2009
DOI: 10.1016/j.seizure.2008.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrence after drug withdrawal in childhood epilepsy

Abstract: Although the decision to discontinue AED treatment necessitates evaluation of each patient individually, our study suggests that female patients and those with abnormal EEG after withdrawal require more cautious follow-up because of the high risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
52
5
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 21 publications
13
52
5
3
Order By: Relevance
“…In previous studies, 85-90% of recurrences were also reported within 2 years. [2310] We found the relapse rate is highest in the 1 st year, with a lower incremental rate after the 2 nd year. In the first 6 months, the recurrence rate was 61.7% after the withdrawal, 26.0% was after 6-12 months and 8.3% in the 12-24 months, and 4.0%) was after 2 years period.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In previous studies, 85-90% of recurrences were also reported within 2 years. [2310] We found the relapse rate is highest in the 1 st year, with a lower incremental rate after the 2 nd year. In the first 6 months, the recurrence rate was 61.7% after the withdrawal, 26.0% was after 6-12 months and 8.3% in the 12-24 months, and 4.0%) was after 2 years period.…”
Section: Discussionmentioning
confidence: 74%
“…They found that 12 patients (6%) had recurrence in the first 3 months after the withdrawal, 16 (8%) had in the 3-9 months period, 10 (5%) had in the 9-15 months period, 2 (1%) had in the 15-24 months period, and 14 (7%) had recurrence after 2 years. [10] In another study, Hindley and Staniforth reported recurrence rate as 32.4% and that cumulative relapse rates were 53.3% of children within 6 months, 66.7% during the 1 st year and 90% within 3 years in their study. [11]…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another situation, also common in childhood epilepsy, is the risky period of tapering the anti-epileptic medication after 2 years of seizure freedom. Although there is no evidence-based knowledge on the length of the tapering period [36], it is well known that withdrawal of anti-epileptic medication should be done slowly and gradually in order to minimize the risk of breakthrough seizures [5,31].…”
Section: When Do Convulsive Seizures Occur?mentioning
confidence: 99%
“…Approximately 30% will be unable to discontinue treatment because of a recurrence of their seizures [4][5][6]. Medication is often restarted and nearly half of the children will become seizurefree a second time, prompting clinicians to consider a second attempt to withdraw AEDs [7].…”
Section: Introductionmentioning
confidence: 99%